22.6% Efficient Solar Cells with Polysilicon Passivating Contacts on n‐type Solar‐Grade Wafers. Issue 11 (1st August 2019) - Basnet, Rabin; Phang, Sieu Pheng; Samundsett, Christian; Yan, Di; Liang, Wensheng; Sun, Chang; Armand, Stephane; Einhaus, Roland; Degoulange, Julien; Macdonald, Daniel
Abstract : Czochralski (Cz)‐grown upgraded metallurgical‐grade (UMG) silicon wafers degrade significantly during high‐temperature processes, eroding their appeal as a low‐cost alternative to conventional electronic‐grade silicon wafers. However, the thermal degradation in UMG wafers can be delayed by utilizing a prefabrication annealing step. Based on this, a high‐efficiency solar‐cell process is modified by selecting a single‐boron diffusion step and applying phosphorus‐doped polycrystalline films as electron‐selective contacts with excellent impurity‐gettering properties to minimize the thermal budget. The application of this modified high‐efficiency solar‐cell process to n‐type UMG‐Cz wafers results in a solar cell with a conversion efficiency of 22.6% on a cell area of 2 × 2 cm 2 . Abstract : The thermal degradation in solar‐grade silicon can be delayed by utilizing a prefabrication annealing step. Based on this, a high‐efficiency solar cell process is modified by selecting a single‐boron diffusion step and applying phosphorus‐doped polycrystalline films as electron‐selective contacts with excellent impurity‐gettering properties which result in a solar cell with a conversion efficiency of 22.6%.